Extra hydrogen bonding interactions by peripheral indole groups stabilize benzene-1, 3, 5-tricarboxamide helical assemblies. Issue 59 (3rd July 2019) - Basuyaux, Gaëtan; Desmarchelier, Alaric; Gontard, Geoffrey; Vanthuyne, Nicolas; Moussa, Jamal; Amouri, Hani; Raynal, Matthieu; Bouteiller, Laurent
Abstract : The indole groups (Ind) of these BTA monomers provide an additional hydrogen bonding interaction that enables the formation of remarkably stable supramolecular helices. Abstract : Benzene-1, 3, 5-tricarboxamide monomers derived from alkyl esters of tryptophan (BTA Trp) self-assemble into helices with an inner threefold hydrogen bond network surrounded by a second network involving the indole N–H groups. As a consequence of this extra stabilization of its helical assemblies, BTA Trp forms more viscous solutions than a range of ester and alkyl BTAs.